Problem Faced by Students in Direct Discussion Session of Speaking Class - Setiawan, Abdilah Bagus Ramadhan Putra; Ramadhan, Novia Syifaputri; Nuradilla, Tiara (International Journal of English Education and Linguistics (IJoEEL), 2021)
Many students found that actively participating in direct discussion sessions of speaking class is hard. There are various problems that they felt whenever they wanted to speak in the class. Thus, this study is aimed to discover what are the major problems encountered by the students in a speaking class which cause low participation during the discussion. This study uses survey research and uses a questionnaire as the instrument. The subjects of this study were 34 students of the English Education Department in the 5th Semester at UIN Syarif Hidayatullah Jakarta. The result of the data analysis shows that there are a variety of problems that students feel when they were in the Speaking class. The issues are related to their lack of confidence, bravery, anxiety, and lack of motivation.